PCC0208057 as a small molecule inhibitor of TRPC6 in the treatment of prostate cancer - Wei, Yingjie; Li, Min; Hu, Yuemiao; Lu, Jing; Wang, Lin; Yin, Qikun; Hong, Xuechuan; Tian, Jingwei; Wang, Hongbo (Frontiers in Pharmacology, 2024)
Prostate cancer (PCa) is a common malignant tumor, whose morbidity and mortality keep the top three in the male-related tumors in developed countries. Abnormal ion channels, such as transient receptor potential canonical 6 (TRPC6), are reported to be involved in the carcinogenesis and progress of prostate cancer and have become potential drug targets against prostate cancer. Here, we report a novel small molecule inhibitor of TRPC6, designated as PCC0208057, which can suppress the proliferation and migration of prostate cancer cells in vitro, and inhibit the formation of HUVEC cell lumen. PCC0208057 can effectively inhibit the growth of xenograft tumor in vivo. Molecular mechanism studies revealed that PCC0208057 could directly bind and inhibit the activity of TRPC6, which then induces the prostate cancer cells arrested in G2/M phase via enhancing the phosphorylation of Nuclear Factor of Activated T Cells (NFAT) and Cdc2. Taken together, our study describes for the first time that PCC0208057, a novel TRPC6 inhibitor, might be a promising lead compound for treatment of prostate cancer.